2015
DOI: 10.1007/s10994-015-5502-3
|View full text |Cite
|
Sign up to set email alerts
|

A computational approach to nonparametric regression: bootstrapping CMARS method

Abstract: Bootstrapping is a computer-intensive statistical method which treats the data set as a population and draws samples from it with replacement. This resampling method has wide application areas especially in mathematically intractable problems. In this study, it is used to obtain the empirical distributions of the parameters to determine whether they are statistically significant or not in a special case of nonparametric regression, conic multivariate adaptive regression splines (CMARS), a statistical machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[17] applied information measure of complexity (ICOMP) as a powerful model selection criterion for the MARS modelling. [18] used Bootstrapping to obtain the empirical distributions of the parameters and to determine whether they were statistically significant or not in a special case of nonparametric regression.…”
Section: Introductionmentioning
confidence: 99%
“…[17] applied information measure of complexity (ICOMP) as a powerful model selection criterion for the MARS modelling. [18] used Bootstrapping to obtain the empirical distributions of the parameters and to determine whether they were statistically significant or not in a special case of nonparametric regression.…”
Section: Introductionmentioning
confidence: 99%
“…The estimator of the multivariate distribution function is used as the basis for the implementation of the Bootstrap method. Yazici et al [8] used the Bootstrap method to obtain the empirical distribution of the parameters in the nonparametric regression of Conic Multivariate Adaptive Regression Splines (CMARS). The results showed that the bootstrap method provides an…”
Section: Introductionmentioning
confidence: 99%